Detection of Legionella Contamination in Tabriz Hospitals by PCR Assay - Mohammad Saeid Hejazi; Mohammad Hossein Soroush; Mohammad Taghi Akhi; Fatemeh Yeganeh Sefidan; Reza Ghotaslou (Tabriz University of Medical Sciences, 2013)
Purpose: The present study was designed to evaluate the occurrence of Legionella contamination in the tap water of Tabriz hospitals, Azerbaijan, Iran. Methods: One hundred and forty water samples from diverse water supply systems of 17 hospitals were collected and analyzed for the presence of Legionella spp. by PCR assay. Results: In this study, 10 of 140 (7.1%) samples were positive for Legionella which L. pneumophila was detected in 4 (2.85%) water samples. Conclusion: In conclusion, hospital potable systems are the primary reservoirs for Legionnaires' disease. This study concludes that Legionella spp. are present in aquatic hospitals environment of Tabriz. Due to the serious risk of infections, it is better to make efforts to eliminate Legionella spp. in water supplies.